Exploring the Landscape of Type 2 Diabetes Mellitus Research: A Comprehensive Review of 670 Scopus-Enrolled Journal Articles (2003-2022) by Pakistani authors - Partab Puri, Amjad Azam, Abdul Rauf Memon, Danish Puri, Syed Zakiuddin, Zameer Hussain Baladi , (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Academics develop ideas, technologies, and creative techniques to promote economic, social, and cultural development through interdisciplinary collaborations and cutting-edge research; Scholarly research shapes educational curriculum. Aim: To associate the authors' connection with various institutes and count the availability of institutes in the study; the research intends to provide insights into the contribution of Pakistani scholars and institutions in this specific area of DM type 2 study. Methods: A retrospective method was utilized for this meta-analysis. "Diabetes mellitus type 2" is written down in the Scopus database's menu bar with "Pakistan' in the following search query as affiliation. Results: Comma separated value (CSV) file was downloaded with 861 documents on the term diabetes mellitus type 2. Seven hundred nineteen articles, 85 review articles, 39 letters, 8 editorials, 3 book chapters, 3 conference papers, 3 notes, and 1 erratum were downloaded. Seven hundred nineteen articles were further analyzed, and 670 were selected for meta-analysis for this study. A total of 2794 authors from 1457 institutes participated in writing 670 articles. 55 authors write 588 articles, 117 authors write 45 articles, 238 authors write 17 articles, and 2384 authors write 20 articles. The extensive participation of authors from a diverse range of institutes (1457 in total) underscores the collaborative nature of diabetes mellitus type 2 researches in Pakistan. Practical Implication: This study can help us learn more about the research done by Pakistani authors and institutions on type 2 diabetes. It also shows us where more research and collaboration are potentially needed to improve Pakistan's scientific efforts in this field Conclusion: The results indicate a strong and cooperative research environment for type 2 diabetes in Pakistani institutions. While the involvement of numerous writers demonstrates the comprehensive and multidisciplinary nature of the research, the concentration of papers among particular authors may indicate specialty or leadership in the topic. The distribution of documents among the various author groups points to broad contributions from a bigger pool of researchers and focused efforts from a smaller group of authors. Keywords: Type 2 Diabetes mellitus, landscape, comprehensive review